Differentiated Di- and Polyboron Compounds: Synthesis and Application in Successive Suzuki–Miyaura Coupling - Xu, Liang; Li, Pengfei (Synlett, 2014)
Differentiated polyboron compounds have emerged as powerful building blocks for modular assembly of complex molecules through selective Suzuki–Miyaura coupling (SMC). Recent progress in this area is briefly reviewed. A novel methodology involving iridium-catalyzed C–H borylation and highly selective SMC toward synthesis and application of this type of building blocks is discussed.
Keywords: polyboron; selective coupling; C–H borylation; modular synthesis